2009
DOI: 10.1177/147323000903700621
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Fluorescent Quantitative Polymerase Chain Reaction Study of Polo-Like Kinase-1 in Pterygia

Abstract: This study was designed to examine the expression of polo-like kinase 1 (PLK1) mRNA in 16 pterygia and 13 normal conjunctival tissue specimens using real-time fluorescent quantitative polymerase chain reaction (PCR). Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as the housekeeping gene. The difference in threshold cycle value (DeltaC(t)) was derived for PLK1 and GAPDH for each sample assayed, and the difference between the paired samples (DeltaDeltaC(t)) was calculated. The mean +/- SD DeltaC(t) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The first group comprised genes involved in mitotic checkpoints and DNA repair. Differential expression of some DNA repair genes in pterygium vs. conjunctiva has been reported in previous gene expression profiling studies [ 44 , 45 ]. The second group comprised genes involved in inflammation and the immune response.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The first group comprised genes involved in mitotic checkpoints and DNA repair. Differential expression of some DNA repair genes in pterygium vs. conjunctiva has been reported in previous gene expression profiling studies [ 44 , 45 ]. The second group comprised genes involved in inflammation and the immune response.…”
Section: Discussionmentioning
confidence: 56%
“…It was previously reported that genes involved in double-strand DNA break repair, RAD50 , RAD51 , XRCC2 and XRCC3 , are differentially expressed in pterygium [ 44 ]. In addition, PLK1 , which regulates the activity of RAD51, was identified as highly expressed in pterygium [ 45 ]. We already had XRCC2 listed; we added RAD50 , RAD51 , RAD51B , RAD51C , RAD51D , and XRCC3 .…”
Section: Resultsmentioning
confidence: 99%
“…From control shRNA-treated RPMI-8226 cells, parental RPMI-8226 cells and DEPTOR shRNA-treated RPMI-8226 cells, total RNA from 1 × 10 6 cells was extracted using TRIzol® reagent (Invitrogen) according to the manufacturer’s instructions and the method of Lu et al. 13 Total RNA (4 µg) was reverse transcribed to cDNA using the ThermoScript™ RT–PCR System Kit (Gibco) according to the manufacturer’s instructions. Primer sequences for RT–PCR for the human DEPTOR were 5′-CCTACCCAAACTGTTTTGTCGC-3′ (sense) and 5′-CGGTCTGCTAATTTCTGCATGAG-3′ (antisense).…”
Section: Methodsmentioning
confidence: 99%
“…From control shRNA-treated RPMI-8226 cells, parental RPMI-8226 cells and DEPTOR shRNAtreated RPMI-8226 cells, total RNA from 1 Â 10 6 cells was extracted using TRIzol Õ reagent (Invitrogen) according to the manufacturer's instructions and the method of Lu et al 13 Total RNA (4 mg) was reverse transcribed to cDNA using the ThermoScript C for 3 min, followed by 35 cycles of denaturation at 95 C for 15s, annealing at 60 C for 30s, and elongation at 72 C for 45s, followed by a final elongation step at 72 C for 10 min. The transcript levels were normalized according to the GAPDH transcripts.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…Total RNA was extracted from 1 × 10 6 HPMCs using TRIzol ® reagent (Invitrogen, Carlsbad, CA, USA), according to the manufacturer's instructions and the method of Lu et al 15 Firststrand cDNA was synthesized from 2-µg aliquots of total RNA by reverse transcription (RT) using the RevertAid™ First Strand cDNA Synthesis Kit (Fermentas Life Sciences, Glen Burnie, MD, USA). Real-time quantitative polymerase chain reaction (PCR) was performed using the Taq 2× PCR MasterMix kit (Tiangen Biochemical Technology, Beijing, China) with SYBR ® Green-based detection chemistry (Invitrogen), on a LightCycler ® Run 5.32 Real-Time PCR System (Roche, Berlin, Germany; 1 µl of cDNA was used in each PCR).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%